Embracing Digital Transformation: Enhancing Insurance Companies' Strategies for a Dynamic Economy (Journal of Universal Science Research, 2023)
This article explores the challenges and opportunities insurance companies face in the digital transformation era and provides insights into improving their strategies to remain competitive and relevant.It emphasizes the importance of embracing insurtech innovations, leveraging big data and analytics, enhancing customer experience, and strengthening cybersecurity to thrive in the digital economy.The article discusses the benefits of adopting agile business models, offering value-added services, and implementing robotic process automation to optimize operations and drive innovation in the insurance industry.